The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijerph191811279
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Work Addiction in Adult Children: The Effect of Addicted Parents and Work Motivation

Abstract: The aim of the study was to examine the mediating role that work motivation plays in the relationship between perceived work addiction of parents and their adult child’s work addiction. The sample was comprised of 537 participants working in different Lithuanian organizations that were selected on the basis of the convenience principle. Data were collected by means of online self-administered questionnaires. To test a mediation model, a structural equation modeling was performed. It was found that perceived wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The descriptive statistics and correlations between the variables analyzed in the study are displayed in Table 3. The means identified in the present research align with the values reported in previous studies conducted by Kuo et al [37], Gegieckaite and Kazlauskas [38], Tóth et al [39], and Morkeviči ūt ė and Endriulaitien ė [40]. Considering that the values obtained for kurtosis and skewness of the study variables were far below the suggested +2/−2 range, all variables appeared to be normally distributed [41]; thus, an adequate normal distribution was expected [42].…”
Section: Descriptive Statistics and Correlationssupporting
confidence: 88%
“…The descriptive statistics and correlations between the variables analyzed in the study are displayed in Table 3. The means identified in the present research align with the values reported in previous studies conducted by Kuo et al [37], Gegieckaite and Kazlauskas [38], Tóth et al [39], and Morkeviči ūt ė and Endriulaitien ė [40]. Considering that the values obtained for kurtosis and skewness of the study variables were far below the suggested +2/−2 range, all variables appeared to be normally distributed [41]; thus, an adequate normal distribution was expected [42].…”
Section: Descriptive Statistics and Correlationssupporting
confidence: 88%
“…Namely, neither the intimacy, nor the autonomy in the family of origin was related to future work addiction of the offspring. On the other hand, parental work addiction , as rated by the offspring, showed a significant, positive, but weak correlation with the work addiction of the adult child [ 31 , 32 ] and it was true for both mothers and fathers of the offspring. Regarding the contradictory results, it is noteworthy that the former study [ 30 ] presents methodological concerns based on our quality analysis, scoring only 43% (see S2 Table ).…”
Section: Resultsmentioning
confidence: 99%
“…While most of the previous studies focused on the consequences of work addiction for an individual itself, we shed light on the role of addicted people in explaining work addiction of others. Moreover, although several studies (e.g., Morkevičiūtė & Endriulaitienė, 2022a, 2022b; Chamberlin & Zhang, 2009; Kravina et al ., 2014) investigated the importance of managers' or parents' addictive behaviors for the employees' well‐being, attitudes and behaviors at work, no research comparing the role of both parents' and managers' work addiction within the context of employee work addiction has been carried out yet.…”
Section: Discussionmentioning
confidence: 99%
“…There are numerous potential explanations of the links between significant others and an individual in terms of work addiction. These include, for instance, external benefits provided by addicted authoritative others for hard work of an individual (Morkevičiūtė & Endriulaitienė, 2022b, 2023a), a narrow understanding of a person's worth when addicted significant others evaluate an individual on account of his/her performance and achievements (Robinson, 2014), over‐responsibility assigned to an individual by addicted significant others (Robinson, 1998, 2014) or even sleep patterns, since poor sleep quality of addicted significant people may control their stress levels, and, ultimately, shape the behavior of those around them (Atroszko & Atroszko, 2020). The following paragraphs introduce the explanatory mechanisms that were most widely discussed in the scientific literature on this field.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation